2018
DOI: 10.1111/1346-8138.14698
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in 892 089 patients with psoriasis in Korea: A nationwide population‐based cohort study

Abstract: The relationship between psoriasis and cancer has not yet been established. The aim of this study was to evaluate the association of psoriasis with certain cancers using national statistics. All patients with psoriasis (n = 892 089; 51.7% male) and age‐ and sex‐matched control subjects (n = 4 460 445) at a 5:1 ratio were enrolled using data from the National Health Insurance Service between 2007 and 2014 in Korea. In psoriatic subjects, overall cancer risk was higher than for subjects without psoriasis after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 41 publications
4
69
3
Order By: Relevance
“…Psoriasis is frequently associated with cardiovascular diseases, metabolic diseases, and renal disorders [25][26][27][28][29][30][31][32][33][34][35][36]. Cancer risk is slightly higher in patients with psoriasis [37]. The topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is frequently associated with cardiovascular diseases, metabolic diseases, and renal disorders [25][26][27][28][29][30][31][32][33][34][35][36]. Cancer risk is slightly higher in patients with psoriasis [37]. The topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that psoriatic patients have elevated risks for the incidence of certain cancers such as lymphoma, possibly due to chronic inflammatory processes [ 8 ]. Regarding MM, a study of > 890,000 psoriasis patients and 4.4 million age- and sex-matched controls showed an elevated incidence of MM in psoriasis patients (HR 1.26 [95% CI 1.07–1.48]) [ 9 ]. Moreover, the use of certain systemic immunotherapies for the management of psoriasis may increase the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the mounting evidence of increased rate of malignancy in psoriatics, studies report conflicting results on the specific types of cancer seen in this population. [1][2][3][4] To provide insight into the risk of malignancy among psoriatics, we performed a retrospective population-based cohort study using a nationally representative sample of the U.S. population. We further compared our results from the national database to a large cohort of patients seen at a tertiary level academic centre.…”
Section: Risk Of Cancer In Psoriasis: Study Of a Nationally Representmentioning
confidence: 99%
“…The observed increased risk is likely multifactorial, potentially related to the inflammatory nature of disease, systemic treatments or increased surveillance. [1][2][3][4] These results suggest that more intensive cancer screening may be warranted for psoriasis patients. Future large population-based cohort studies are needed to further assess the independent risk of specific malignancies in this population.…”
Section: Risk Of Cancer In Psoriasis: Study Of a Nationally Representmentioning
confidence: 99%